Diagnostikovanie urovne zotavovacich procesov v treningu biatlonistiek - Augustin, M.; Moravec, R. (Physical Education and Sport, 2002)
In the process of the improvement of the practice it is the most important for the trainer/coach to understand the system of selfregulation of the sportsman's body. The authors of the research were observing the biathloner-woman for three week at sport camp, they were trying to find sequences between the parametres of variability of heart beat measured in the morning after waking up and her subjective feelings about the reconvalescent after the practice, which she took part a day before. The results of the research confirmed, that according to the observation of the variability of heart beat we can come to a certain conclusion about the causes and mechanism of the tireness of the athlete and the current coordination of practice influence. In spite of the fact that the feelings of the athlete do not always need to be objective indicators about the state of her condition, more important seemed to be the knowledge about the difference of aimed deflection from the average R-R interval (stda-stdb) as the oscilation of basal heart beat. Eine grundsätzliche Bedeutung für den Trainer bei der Steuerung des Trainingsprozesses hat die Einsicht in die Prozesse der Selbstregulation des Sportlers. Bei einer Sportlerin im Biathlon haben wir während eines dreiwöchigen Campus die Zusammenhänge zwischen den Parametern der Ruhe-Herzfrequenz nach dem Aufwachen und ihren subjektiven Empfindungen über Erholung nach dem Training, das sie ein Tag früher absolviert hat, gesucht. Die Ergebnisse haben gezeigt, dass es möglich ist, auf Grund der Beobachtung der Pulsfrequenz teilweise auf die Ursachen und Mechanismen der Ermüdung des Sportlers zu schliessen und das Training durchgehend zu korrigieren.